2022
DOI: 10.3389/fgene.2022.1050341
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses of a mitophagy-related gene signature for predicting prognosis in patients with uveal melanoma

Abstract: We aimed to create a mitophagy-related risk model via data mining of gene expression profiles to predict prognosis in uveal melanoma (UM) and develop a novel method for improving the prediction of clinical outcomes. Together with clinical information, RNA-seq and microarray data were gathered from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. ConsensusClusterPlus was used to detect mitophagy-related subgroups. The genes involved with mitophagy, and the UM prognosis were discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“… 6 Mitochondrial dysfunction is closely associated with extensive diseases due to reduced ATP synthesis, excessive ROS generation, mitochondrial dynamics disorder, and abnormal mitophagy initiation. 7 , 8 Li et al. found that icariside II can balance mitochondrial dynamics and reduce oxidative stress after AMI by stimulating the nuclear factor erythroid 2-related factor 2 (Nrf2)/sirtuinf 3 (SIRT3) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Mitochondrial dysfunction is closely associated with extensive diseases due to reduced ATP synthesis, excessive ROS generation, mitochondrial dynamics disorder, and abnormal mitophagy initiation. 7 , 8 Li et al. found that icariside II can balance mitochondrial dynamics and reduce oxidative stress after AMI by stimulating the nuclear factor erythroid 2-related factor 2 (Nrf2)/sirtuinf 3 (SIRT3) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%